Dynamic Water Hydrogen-Bond Networks at the Interface of a Lipid Membrane Containing Palmitoyl-Oleoyl Phosphatidylglycerol - Karathanou, Konstantina; Bondar, Ana-Nicoleta (The Journal of membrane biology, 2018)
Lipid membrane interfaces are complex environments that host essential cellular processes such as binding of proteins or drug molecules. A key open question is how water molecules at the interface of membranes with anionic lipids participate in protein binding. To address this question, we studied the dynamics of water hydrogen bonding at the interface of membranes composed of phosphatidylcholine and phosphatidylglycerol, and implemented an algorithm to identify hydrogen-bonded networks at the interface of a lipid membrane, and to characterize their dynamics and linear connections. We find that the membrane interface is characterized by a rich network of hydrogen-bonded water chains that bridge lipid headgroups, some of which form transient lipid clusters. Water-mediated bridges between with lipid phosphate groups are dynamic, with residence lifetimes on the order of picoseconds. These clusters of water/lipid headgroup hydrogen bonds could provide a platform for the binding of proteins or of drug molecules with cationic groups.